Survey of horse transportation in Australia: issues and practices. Issue 10 (27th September 2016) - Padalino, B; Raidal, SL; Hall, E; Knight, P; Celi, P; Jeffcott, L; Muscatello, G
Abstract : Objective: To survey amateur and professional participants on equine transportation management, practices and outcomes in Australia. Methods: An online survey targeting people who organised horse movements at least monthly was made available to a broad cross‐section of amateur and professional equine associations. Respondents were invited to provide demographic details and information relating to their routine transportation management practices and their experiences of issues relating to the transportation of horses. Results: Of 797 usable responses involving approximately 17, 000 horses and 313, 000 individual horse transport events, transport‐related behavioural problems were reported by 38% of respondents, particularly at loading. Transport‐related health problems had been experienced during or after transportation by horses in the care of 67% of respondents. The most common problems reported were traumatic injuries (45.0%), diarrhoea (20.0%), muscular problems (13.0%), respiratory problems (12.3%), overheating (10.5%) and colic (10.3%). In the 2 years reviewed in the survey, 9.4% of participants reported at least one case of transport‐associated pneumonia and 35 horses had died, most commonly from fractures, colic or pneumonia. Although respondents identifying as amateurs transported horses less frequently and over shorter distances, the incidence of transport‐related problems was similar between amateurs and professionals. Respondents reported specific precautions before, during and after transportation, although management was often not compliant with the Australian Code of horse transportation. Conclusions: Responses indicated that there remains a substantial risk of adverse welfare and health outcomes for horses transported in Australia and management practices reported may not be compliant with current recommendations for transportation.